First Report of Resistance to Glyphosate in Several Species of the Genus Echinochloa in Argentina - Cortés, Eduardo José (2023)
The genus Echinochloa consists of about 33 species worldwide; some of these are weeds that are very difficult to control in Argentina, and only E. colona was reported as resistant to glyphosate. The objective of this work is to determine if one or more populations of E. colona, E. crus-galli, E. oryzoides, and E. chacoensis are resistant to or less susceptible to glyphosate. Between 2015 and 2017, seeds of different Echinochloa populations were collected from the provinces of Córdoba, Santa Fe, Buenos Aires, and Entre Ríos, all from fields with a history of at least 10 consecutive years of glyphosate application and complaints from farmers due to failures in control. With these populations, survival, dose–response, and shikimic acid quantification tests were carried out to determine their level of susceptibility to glyphosate. The results obtained allow us to report the first worldwide case of resistance to glyphosate in populations of E. crus-galli, E. oryzoides, and E. chacoensis and expand the information on E. colona.